Importance of Speech Disorders in Cleft Lip and Palate Patients, Assessment of Speech Therapy and Evaluation of Distraction Osteogenesis: Two Case Reports - Ruhi Nalçacı; Seyhun Topbaş; Metin Orhan; Cenk Doruk (Galenos Yayinevi, 2009)
The aim of this study is to spotlight on; what should be taken into consideration during and after surgery to prevent and/or to correct speech pathologies of the CLP patients, insufficiency of the treatment without speech therapy, and remarkable changes achieved with speech therapy. For this purpose, 21 years old female patient with late operated soft palate cleft, suffering from only her speech problems, and a 21 years old female patient with bilateral CLP operated in early ages, but had oronasal fistula and, suffering from her speech, aesthetic and functional problems are presented. The first patient was treated by a specialist speech therapist. After eight months of rehabilitation, it was observed that articulation errors of the patient were reduced and speech comprehensibility was improvedIn the second case, the maxilla was advanced with "Posterior Maxillary Segmental Sagittal Distraction". After the distraction period patient's profile was improved. The existing velopharyngeal insufficiency did not increase after distraction and positive improvement was observed in speech mimics. Correction of aesthetics and occlusion alone in the CLP patients is not sufficient and it is not possible to expect correction of speech with improvement of the peripheral structures. Without "speech therapy" it is not possible to correct or optimize speech.